The Amhara Regional Report : Public Finance Review - Alebachew, Abebe; Alemu, Getnet (World Bank, Washington, DC, 2013)
The objective of this study is explore in depth public finance issues and their impact on decentralized service delivery at the regional and woreda level in Amhara region. The study is carried out as part of the federal and some regional case studies designed to examine effectiveness of public finances of sub-national governments. This study was expected to (i) review the institutional arrangement for managing public finances at the regional level including policies, budgetary institutions, systems and processes; (ii) assess the level, trend, and composition of public spending (both functional and economic classification) in per capita terms over the past five years and identify key achievements and limitations; (iii) assess the level, trend, and, composition of revenue at the regional level and examine the financing framework, including ways to increase local revenue generation capacity; (iv) assess the role of external aid in supporting decentralized service delivery and the sustainability of the program in absence of external aid; (v) review the planning and budgeting process as well as the quality of PFM system; and (vi) data permitting, establish the link between the level of spending and the outputs and outcomes for selected sectors. The study used standard public financial process review methodologies used for undertaking PEFA assessments. The report reviewed the various studies, plans and performance reports of the various sectors in the regions between EFY 1997 and 2001. In addition, key informant interviews were carried out at bureaus levels and woreda offices of education, health, water, agriculture and rural development, finance and economic development, revenue, General Auditor, rural road and woreda administrations.